DISORIENTASI AMIL ZAKAT DIERA DISRUPSI - Pertiwi, Hana; Atika, Atika; Abdilah, Muhammad (Program Studi Muamalah Fakultas Syariah dan Hukum, 2024)
Zakat is part of the pillars of Islam, where the distribution and distribution must be on target, carried out by a competent zakat amil. This study aims to complement existing deficiencies by analyzing how the Zakat Amil is disoriented in the era of disruption, so that the Zakat Amil is able to carry out its duties and functions well. The approach in this paper is descriptive qualitative, using library research studies with Google searches related to the title. This paper asks 3 important questions that must be found for solutions, including: (a) what are the dynamics of amil zakat in the era of disruption; (b) what are the factors that cause disorientation of zakat amil in the era of corruption; (c) what are the implications of the disorientation of amil zakat in the era of disruption. This article shows that there is a need for regulations that clearly provide legality for zakat amil, provide training for zakat amil and provide sanctions when zakat amil carry out Pangelinan outside the predetermined regulations. The impact that occurs will cause the continuation of amil who always takes wrong actions if training is not carried out on Pangelinan zakat funds and there will be no deterrent effect if there are no sanctions that are enforced.